1973
DOI: 10.1136/thx.28.6.742
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effect of guaiphenesin on mucociliary clearance from the human lung

Abstract: . A preliminary study ofthe effect of guaiphenesin on mucociliary cleaance from the human lung. The effect of guaiphenesin (administered as Robitussin1) on mucociliary clearance has been assessed in 15 subjects from the rate of removal from the lung of previously inhaled radioactive tracer particles. The guaiphenesin was compared with a positive control preparation consisting of the guaiphenesin vehicle only in two double-blind crossover trials. The first trial examined eight aged 'healthy' volunteer subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…11 Guaifenesin belongs to the class of drugs known as expectorants and exerts its effects via indirect and direct mechanisms. The rate of mucociliary clearance is enhanced by guaifenesin 12 and guaifenesin has demonstrated an expectorant effect in patients with productive coughs. 13 Following oral administration, guaifenesin is rapidly and completely absorbed from the gastrointestinal (GI) tract, and C max of the unchanged active substance is observed between 15 and 30 min.…”
mentioning
confidence: 99%
“…11 Guaifenesin belongs to the class of drugs known as expectorants and exerts its effects via indirect and direct mechanisms. The rate of mucociliary clearance is enhanced by guaifenesin 12 and guaifenesin has demonstrated an expectorant effect in patients with productive coughs. 13 Following oral administration, guaifenesin is rapidly and completely absorbed from the gastrointestinal (GI) tract, and C max of the unchanged active substance is observed between 15 and 30 min.…”
mentioning
confidence: 99%
“…Although it has been shown to help with the common cold, long-term use of guaifenesin has not been shown to be of benefit in COPD or CB (74). Inhaled hypertonic saline works not only by rehydrating mucus by drawing water from epithelial cells but also by promoting cough (75,76).…”
Section: Expectorants and Mucolyticsmentioning
confidence: 99%
“…10 However, two other studies 11,12 found no effect of this drug on cough due to chronic bronchitis. Another expectorant, iodinated glycerol, has been found to be active in reducing subjective assessments of cough frequency and severity in patients with chronic bronchitis in two studies.…”
Section: Drugs That Affect Mucociliary Factorsmentioning
confidence: 98%